A survey of visitor satisfaction at Victoria Falls Rainforest - Zhou, Zibanai (Africa Journals, 2021)
The study investigated the level of visitor satisfaction at the ecological Victoria Falls rainforest. Ten anchor elements drawn from literature were used to measure visitor satisfaction level. A questionnaire survey was purposively administered on 300 tourists at the protected area`s main exit point. Findings demonstrated that high levels of visitor satisfaction exist particularly in leisure, educational and repeat visitors. Satisfaction ratings were high on most variables. Visitors were mostly impressed by easy air connectivity to the Victoria Falls, an expansive range of activities in the rainforest, good quality of services and facilities, and an efficient and hospitable staff. Results further showed that the majority of visitors were keen to return to the rainforest in the medium to long term, ready to recommend the rainforest to others back home, and had an improved post visit image not only of Victoria Falls but also of destination Zimbabwe as a whole. On the flip side, a few international visitors had a dim view on numerous road blocks along the highway to Victoria Falls, vendor menace in the CBD, and steep rainforest entrance fees. Findings have implications in that they directly speak to pertinent policy issues critical to the success and development of the tourism industry, which are, the need for policy congruency between and within government departments and ministries, review of the tourism pricing model, and capacitating of the tourism police service to deal with the vendor menace.